2016
DOI: 10.1073/pnas.1615902113
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the mitochondrial ATP synthase from Pichia angusta determined by electron cryo-microscopy

Abstract: The structure of the intact monomeric ATP synthase from the fungus, Pichia angusta, has been solved by electron cryo-microscopy. The structure provides insights into the mechanical coupling of the transmembrane proton motive force across mitochondrial membranes in the synthesis of ATP. This mechanism requires a strong and integral stator, consisting of the catalytic α3β3-domain, peripheral stalk, and, in the membrane domain, subunit a and associated supernumerary subunits, kept in contact with the rotor turnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 45 publications
6
42
0
Order By: Relevance
“…4) and that therefore the multiple bands on the native gel are artifactual. It is likely that the removal of the c-ring and accompanying loss of subunits ATP6 and ATP8 destabilizes the dimerization interface, which probably relies on subunits e and g and may also depend on supernumerary subunits f, DAPIT, and 6.8PL (17,18). It is also possible that the vestigial complex remains dimeric in the membrane and that it is destabilized (monomerized) artifactually by the extraction process.…”
Section: +mentioning
confidence: 99%
See 3 more Smart Citations
“…4) and that therefore the multiple bands on the native gel are artifactual. It is likely that the removal of the c-ring and accompanying loss of subunits ATP6 and ATP8 destabilizes the dimerization interface, which probably relies on subunits e and g and may also depend on supernumerary subunits f, DAPIT, and 6.8PL (17,18). It is also possible that the vestigial complex remains dimeric in the membrane and that it is destabilized (monomerized) artifactually by the extraction process.…”
Section: +mentioning
confidence: 99%
“…Recent cryo-electron microscopy analyses of the ATP synthase complexes suggest that at least subunits e and g are involved in the interface between monomers of the ATP synthase in the dimeric complexes (17,18). The gene disruption strategy followed for the c-subunit provides a possible approach toward resolving the issue of whether any or all of these subunits are involved in forming the PTP.…”
Section: +mentioning
confidence: 99%
See 2 more Smart Citations
“…S4). Furthermore, mapping of a homology model of ATP8 to cryo-EMderived structures of ATP synthase in multiple rotational states (55) revealed that links between ATP8 (K46 and K48) and the rotor subunit ATPD (K136) are possible only with ATP synthase rotational state 3. In contrast, the link between ATP8 (K48) and the rotor subunit ATP5E (K50) was possible only in rotational state 1 (Fig.…”
Section: Protein Sitementioning
confidence: 99%